cAMP-PKA signal transduction specificity in Saccharomyces cerevisiae - Portela, Paula (2020)
Living cells have developed a set of complex signaling responses, which allow them to withstand different environmental challenges. Signaling pathways enable the cell to monitor external and internal states and to articulate the appropriate physiological responses. Cellular signal transmission requires the dynamic formation of spatiotemporal controlled molecular interactions. One of the most important signaling circuits in Saccharomyces cerevisiae is the one controlled by cAMP-Protein Kinase A (PKA). In budding yeast, extracellular glucose and a plethora of signals related with growth and stress conditions regulate the intracellular cAMP levels that modulate PKA activity which in turn regulates a broad range of cellular processes. The cAMP-PKA signaling output requires a controlled specificity of the PKA responses. In this review we discuss the molecular mechanisms that are involved in the establishment of the specificity in the cAMP-PKA signaling pathway in S.cerevisiae.